Intravenous Diclofenac vs. Tramadol infusion for Post-operative Pain Management: A Randomized Trial - Binay, Thakur; Mukti, Devkota; Krishna, Khanal; Bishal, Sapkota (Nepalese Journal of Cancer, 2018)
Purpose: The study was conducted to compare the analgesic and adverse effect profiles of intravenous infusion of Tramadol and Diclofenac in post-operative pain management. Method: Cancer patients undergoing major surgery were prospectively randomized into two groups of 35 and was entered into single blinded clinical trial. Patients in each arm received either Tramadol (Gr A) or Diclofenac Infusion (Voveran®) (Gr B) for first 48 hours after surgery. Pain intensity was measured based on a 10 point Verbal Rating Scale (VRS). VRS was obtained at 6, 12, 18, 24, 30, 36, 42 and 48 hrs post-operatively. Result: The mean age was 56.3 and 49.5 years in Gr A and B, respectively (p=.056). Mean length of incision was 16.46 cm and 18.23 cm in Gr A and B, respectively (p=.1). On 0 post-operative day, 14 patients in Gr A and 6 patients in Gr B required accessory analgesics (p=.18). On 1st post-operative day, 2 patients in Gr A and 1 patient in Gr B required accessory analgesics (p=.6). One patient on Tramadol group had nausea post-operatively. Average cost was 471.73 and 227.80 Nepali rupees in Gr A and Gr B, respectively (p=.032). Conclusion: Intravenous infusion of Diclofenac should be considered as a safe and cheaper alternative to Tramadol infusion for pain management after major surgical oncological procedures.